Hubungan Kurikulum Pendidikan Tahap Sarjana terhadap Kompetensi Mahasiswa pada Tahap Profesi di Rumah Sakit Pendidikan - Nurfitri Bustamam; Runinda Pradnyamita; Citra Ayu Aprilia; Wahyukarno Wahyukarno (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: In 2010, students of Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta who were graduated from the competency-based curriculum (CBC) in pre-clinical phase have entered the teaching hospital for their clinical rotation phases, while students who were graduated from the conventional curriculum still learned in the same teaching hospital. This study aimed to evaluate the students competencies during the clinical rotation phase, between students who were graduated from CBC compare to students who were graduated from conventional curriculum.Method: This was a cross sectional study using 4-point Likert scale questionnaire. The population of this study were all students in clinical stage at Gatot Soebroto Hospital. The sample were 40 students from each group. Data was collected from December 2010 to January 2011. Chi-square test was used to analyze the data.Results: This study showed that the students competencies in CBC curriculum were higher in CBC significant correlation between pre-clinical curriculum with student’s competencies in communication and behavior (p= 0.006), science session and scientific report (p=0.000), and physical examination (p=0.000).However, it is found that there were no correlation between pre-clinical curriculum with student’s competencies in history taking, laboratory examination, making a diagnosis, and patient management (p > 0.05).Conclusion: Student competencies higher in CBC curriculum compare to conventional curriculum, and particularly significant in physical examination, communication & behavior and scientific report & science session competencies.